2019
DOI: 10.2174/1574884714666190524100214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mean Minimum Dose of Bolus Oxytocin for Proper Uterine Contraction during Cesarean Section

Abstract: Background: Cesarean section is the most common midwifery operation. The aim of this study is to determine the mean minimum dose of bolus oxytocin for proper uterine contraction during cesarean section. Method: Patients were divided into two groups: elective cesarean section (n=41) and cesarean section due to difficulty in labor (n=42 patients). Patients underwent spinal anesthesia and oxytocin infusion was begun at 30 drops per minute (20 units of oxytocin per 1000 cc serum), and was also administered as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In another largescale study conducted in Egypt, 10 IU IV bolus oxytocin was found to be superior to 10 IU IM oxytocin in vaginal delivery (9). However, the other systematic review could not establish whether the IV or IM route was superior and concluded that larger randomized control trials were required in this regard (10). The hemodynamics of the patients were stable in both groups and no difference was found between the groups in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…In another largescale study conducted in Egypt, 10 IU IV bolus oxytocin was found to be superior to 10 IU IM oxytocin in vaginal delivery (9). However, the other systematic review could not establish whether the IV or IM route was superior and concluded that larger randomized control trials were required in this regard (10). The hemodynamics of the patients were stable in both groups and no difference was found between the groups in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The mean dose of opioid required was least with 10 mg melatonin, followed by 5 mg melatonin and placebo group, showing that melatonin is likely to be associated with dose-dependent decrease in the need of opioid following cesarean section [ 29 ]. The mean time interval between surgery and resumption of the physical activity was also least with high dose of melatonin (10 mg) relative to two other groups [ 30 ]. Side effects were insignificantly correlated in all three groups.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study carried out by Beiranvand et al concluded that the minimum effective dose is 1 IU, and in those in labor progress 1–1.5 IU, both followed by 20 IU oxytocin in 1000 mL infusion [ 32 ]. The previously mentioned up-down sequential method study of Carvalho also resulted in a small minimum effective dose.…”
Section: Discussionmentioning
confidence: 99%